Influence of the content of stacked ZnO on the structural and optical properties of heterostructured ZnO/Ga2O3 films - Peverga R. Jubu; E. Danladi; M.B. Ochang; O. Adedokun; C.C. Amadi; D.D. Hile; W.V. Zhiya; A.A. Iorokpen; Y. Yusof; F.K. Yam (Optical Materials: X, 2024)
The rising demand for heterojunction materials stimulated by the great achievements of modern nanotechnology has triggered enormous interests in the investigation of their materials properties. Heterostructured ZnO/Ga2O3 has been deployed for different device applications, but its several optical parameters have rarely been investigated. The present work attempts to investigate the influence of the thickness of stacked ZnO layer on the surface of Ga2O3 film. Optical parameters, such as absorption and extinction coefficient, Urbach energy, refractive index, dielectric constants, optical dispersion energy, single oscillator energy, static refractive index, oscillator strength, and oscillator wavelength of the ZnO/Ga2O3 films were studied. Morphological characterization showed microstructures of various shapes. Cross-section measurements showed that the thickness of the Ga2O3 layer remained approximately the same for all samples, while the thickness of the ZnO layer increased from 0 to 5.14 nm. Structural analysis revealed the coexistence of β-Ga2O3 and wurtzite ZnO crystal phases. UV–Vis absorption spectra demonstrated two distinct absorptions belonging to the β-Ga2O3 and ZnO. The bandgap of the composite ranged between 4.43 and 4.69 eV with an increase in the amount of ZnO at the surface. The absorption and extinction coefficient were in the order of 103 cm−1 and 10−5, respectively. The Urbach energy ranged between 0.688 and 1.125 eV. The refractive index was in the range 2.09–2.85, while the static refractive index ranged between 1.90 and 2.73. Also reported were other optical parameters, such as the real and imaginary dielectric constant, dispersive energy, single oscillator energy, oscillator strength, and oscillator wavelength.